Assessment and Mitigation of Exposure of 3-D Printer Emissions - Kim, Boowook; Shin, Jae Hoo; Kim, Hoi Pin; Jo, Mi Seong; Kim, Hee Sang; Lee, Jong Sung; Lee, Hong Ku; Kwon, Hyuk Cheol; Han, Sung Gu; Kang, Noeul; Gulumian, Mary; Bello, Dhimiter; et al. (Frontiers in Toxicology, 2022)
This study monitored particulates and volatile organic compounds emitted from 3-D printers using acrylonitrile-butadiene-styrene copolymer (ABS) filaments at a workplace to assess exposure before and after introducing exposure mitigation measures. Air samples were collected in the printing room, and adjacent corridor, and real-time measurements of ultrafine and fine particle monitoring were also conducted. Extensive physicochemical characterization of 3-D printer emissions was performed, including real-time (size distribution, number concentration) nanoparticle characterization, size-fractionated mass distribution and concentration, as well as chemical composition for metals by ICP-MS and volatile organic compounds (VOCs) by GC-FID, real-time VOC monitors, and proton-transfer-reaction time-of-flight mass spectrometer (PTR-TOF-MS). Air sampling showed low levels of total suspended particulates (TSP, 9-12.5 /m3), minimal levels (1.93-4 ppm) of total volatile organic chemicals (TVOC), and formaldehyde (2.5-21.7 ppb), with no detectable levels of styrene. Various harmful gases, such as formaldehyde, acrolein, acetone, hexane, styrene, toluene, and trimethylamine, were detected at concentrations in the 1-100 ppb by PTR-TOF-MS when air sample was collected into the Tedlar bag from the front of the 3-D printer. Ultrafine particles having an average particle size (30 nm CMD and 71 nm MMAD) increased during the 3-D printing operation. They decreased to the background level after the 3-D printing operation, while fine particles continually increased after the termination of 3-D printing to the next day morning. The exposure to 3-D printer emissions was greatly reduced after isolating 3-D printers in the enclosed space. Particle number concentration measured by real-time particle counters (DMAS and OPC) were greatly reduced after isolating 3-D printers to the isolated place.